The development of a new variable stiffness soft gripper. (9th October 2019) - Tang, Zhijie; Lu, Jiaqi; Wang, Zhen; Ma, Gaoqian
A new variable stiffness four-finger soft gripper with a combination of rigid and soft structures is designed. The combination of rigid and soft structures is one of the methods to improve the performance of soft grippers. Grasping motion is achieved by the rigid structure of the screw and the connecting rod. Soft gripper uses human finger-like structure made of silicone, and the air pressure and the rigidity of the soft fingers can be adjusted by the air pump. The soft gripper overcomes the inability of a rigid gripper to easily and safely grasp soft and brittle objects and the inability of a completely soft gripper to exert sufficiently high forces to achieve effective grasping. Grasping force can be improved by increasing the stiffness of the finger and the driving stroke of screw. The variable grasping force allows the soft gripper to grasp different shape objects, specially soft and brittle objects.